Comparative efficacy of two medicinal plants and Amaryl® tablet (Glimepiride) in induced diabetes mellitus in rat - Das, PC; Mostofa, M; Sarkar, AK; Ali, M (Journal of the Bangladesh Agricultural University, 2010)
Comparative efficacy of two indigenous herbal extracts, (Trigonella foenum-graecum seed & Coccinia indica leaves) with the commonly used drug Glimepiride were studied. Healthy young rats (n=30) of both sexes weighting between 150 to 200 gm were selected and divided into six equal groups, as A (Control), B (diabetic), experimental diabetic groups were-C, D, E and F, treated with combined extract of Methi seed and Telakucha leaves- @ 250mg, 500mg, 750mg and Glimepiride 800μg/kg body weight, respectively. The substances were given orally once daily for14 days. The blood glucose concentration were decreased significantly (P<0.01) in groups C, D, E, and F. The body weight increased significantly (P<0.05) by 2.3%, 3.9%, 4.8% and 10.4%, respectively. The herbal extracts significantly reduced in blood glucose level with the increased in body weight. It is indicated that antidiabetic activity of Trigonella foenum-graecum and Coccinia indica are evident that are traditionally used as the herbal preparations by the Ayurvedic practitioners for the control of diabetes mellitus. Keywords: Trigonella foenum graecum; Coccinia indica; Amaryl® Tablet (Glimepiride); Streptozotocin and antidiabetic effect; Diabetes mellitus; Rat DOI: 10.3329/jbau.v6i2.4825 J. Bangladesh Agril. Univ. 6(2): 297-300, 2008